Influence of natural weathering on colour stability of materials used for facial prosthesis - Santos, Daniela Micheline dos [UNESP]; Goiato, Marcelo Coelho [UNESP]; Sinhoreti, M. A C; Moreno, A. [UNESP]; Dekon, Stefan Fiuza de Carvalho [UNESP]; Haddad, M. F. [UNESP]; Pesqueira, Aldieris Alves [UNESP] (Taylor & Francis, 2012)
Colour stability of resin and silicone is an important factor for longevity of facial prostheses. The aim of this study was to evaluate the colour stability of resins and silicone for facial prostheses. Three brands of acrylic resin and one of facial silicone were evaluated considering pigment incorporation for the colourless materials. Ten samples of each material were fabricated and submitted to measurements of chromatic alteration initially and after 90 and 180 days of weathering natural through visual analysis and spectrophotometry. Data were evaluated by ANOVA and Tukey test (p < 0.05). Statistically significant colour alteration was observed among some materials regardless of the period. The materials did not present a statistical difference between 90 and 180 days except for the pigmented heat-polymerized resin. The colour difference between pigmented Silastic MDX4-4210 and colourless Silastic was statistically significant (p < 0.01) in both periods as well as between pigmented and colourless heat-polymerized resin, and between the resins Rapidaflex and Lentaflex. The visual method demonstrated colour alteration in all materials evaluated during the first 90 days of ageing. All materials exhibited colour alteration due to exposure to environment. © 2012 Informa UK, Ltd.
Keywords: Colour stability; Facial prostheses; Natural weathering; Polymers; Acrylic resins; Colour differences; Facial prosthesis; Silastic; Statistical differences; Visual analysis; Color; Materials; Natural polymers; Rating; Resins; Silicones; Stability; Weathering; Prosthetics; acrylic acid resin; polymer; rain; silicone derivative; analysis of variance; chemistry; humidity; materials testing; maxillofacial prosthesis; prosthesis; spectrophotometry; ultraviolet radiation; Acrylic Resins; Analysis of Variance; Humidity; Materials Testing; Maxillofacial Prosthesis; Prosthesis Coloring; Rain; Spectrophotometry; Ultraviolet Rays